Peran Sitoglobin pada Kanker - Yastani, Deasyka; H, Novi Silvia; Jusman, Sri Widia A (Jurnal Biomedika dan Kesehatan, 2023)
Cytoglobin (Cygb) is a new member of the globin protein family, following the discovery of other globin proteins such as hemoglobin (Hb), myoglobin (Mb), and neuroglobin (Ngb). In 2001, Kawada et al. identified Cygb in hepatic stellate cells (HSCs) that play an important role in the repair of damaged liver cell tissue, hence the name stellate cell activation-associated protein (STAP). Cygb has a more universal role than Hb, Mb, and Ngb, and is expressed throughout mammalian tissues. Cygb is a globin with 6 coordination bonds (hexacoordinate globin). Cygb has been shown to play an important role in the normal cell respiratory chain, including oxygen storage, destruction of reactive oxygen species (ROS), terminal oxidase activity, regulation of fibrogenesis, and regulation of apoptosis. The role of Cygb in the respiratory process has been studied because it is associated with the globin family, and because of the upregulation of Cygb during hypoxia, but its specific role has not been elaborated. Recent research reports that Cygb has several implications for cancer. In most cancer cells, Cygb expression is upregulated by hypermethylation, suggesting epigenetic control. In cancer cells, downregulation of Cygb occurs which indicates a possible role as a tumor suppressor gene. In some malignancies, on the contrary, Cygb upregulation may be associated with resistance to hypoxia which indicates Cygb has two sides or Janus faces related to its role in cancer cells.